International Researchers in Japanese Companies - Li, Ming; Huang, Futao (International Higher Education, 2022)
To develop global human resources and improve the international competitiveness of Japan’s industry and business, Japanese companies have made efforts to attract excellent international researchers, expecting them to play an active role in their workplaces. This article explores some aspects of their personal identities, their motivations, work roles, and contributions, as well as the challenges that they face, compared with international faculty employed at Japanese universities.